2022
DOI: 10.2147/cia.s388319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Influencing Sarcopenia Among Community-Dwelling Older Adults Using the Asian Working Group for Sarcopenia Definition

Abstract: Objective This study aimed to explore the prevalence and impact of related factors for sarcopenia among community-dwelling older people in Chongming district, China, according to the diagnostic criteria of the Asia Working Group for Sarcopenia-2019. Methods We conducted a cross-sectional study from April 2021 to December 2021. Diagnosis of sarcopenia (non-sarcopenia, possible sarcopenia, sarcopenia, and severe sarcopenia) was based on appendicular skeletal muscle mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
6
0
2
Order By: Relevance
“…(Z. Chen et al, 2022;Cheng et al, 2021;Darroch et al, 2022;de Souza et al, 2021;Delibaş et al, 2021;Gao et al, 2021;He et al, 2022;Jin et al, 2021;Kirk et al, 2021;Kitamura et al, 2020;Kurita et al, 2021;Lee & Lee, 2023;Lin et al, 2022;Lu et al, 2023;Nunes et al, 2021;Suzan et al, 2022;Tan et al, 2022;Zhang et al, 2022). En la tabla 1 se muestran las características y principales resultados de los estudios que incluyeron un análisis transversal.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…(Z. Chen et al, 2022;Cheng et al, 2021;Darroch et al, 2022;de Souza et al, 2021;Delibaş et al, 2021;Gao et al, 2021;He et al, 2022;Jin et al, 2021;Kirk et al, 2021;Kitamura et al, 2020;Kurita et al, 2021;Lee & Lee, 2023;Lin et al, 2022;Lu et al, 2023;Nunes et al, 2021;Suzan et al, 2022;Tan et al, 2022;Zhang et al, 2022). En la tabla 1 se muestran las características y principales resultados de los estudios que incluyeron un análisis transversal.…”
Section: Resultsunclassified
“…Por su parte, en las investigaciones realizadas por Chen et al (2022), de Souza et al (2021, He et al (2022), Kitamura et al (2020) y Kurita et al (2021), se observó que la prevalencia de sarcopenia era significativamente mayor en el grupo de adultos mayores con síntomas depresivos, en comparación con el grupo sin depresión, reportando los momios en un rango de 1.68 a 2.65.…”
Section: Discussionunclassified
“…For instance, Liu et al [ 42 ] found that, in Chinese adults ≥ 50 years, the prevalence of sarcopenia according to different operational definitions were 11.8% (EWGSOP2), 18.1% (FNIH), 22.8% (AWGS 2019), 24.1% (IWGS), and 57.1% (EWGSOP1). However, there are other factors such as age group, gender, geographical areas, ethnicities, or locations that may affect the prevalence of sarcopenia [ 43 , 44 ]. A meta-analysis published by Petermann-Rocha et al [ 45 ] described that the prevalence of sarcopenia varied from 10% to 27% in adults aged 60 years and over, where the highest prevalence was found in Oceania (EWGSOP1) and the lowest in Europe (EWGSOP2).…”
Section: Discussionmentioning
confidence: 99%
“…SMI was calculated by dividing the CSA, measured at the C3 vertebra level on CT scans by the square of the patient's height in meters 24 . Subjects with SMI < 41 cm 2 /m 2 in females, <43 cm 2 /m 2 in underweight or healthy weight males, and <53 cm 2 /m 2 in overweight or obese males were considered sarcopenic for the purposes of this study 25‐31 …”
Section: Methodsmentioning
confidence: 99%
“…24 Subjects with SMI < 41 cm 2 /m 2 in females, <43 cm 2 /m 2 in underweight or healthy weight males, and <53 cm 2 /m 2 in overweight or obese males were considered sarcopenic for the purposes of this study. [25][26][27][28][29][30][31]…”
Section: Data Collectionmentioning
confidence: 99%